2006
DOI: 10.1121/1.2151816
|View full text |Cite
|
Sign up to set email alerts
|

Phase effects in masking by harmonic complexes in birds

Abstract: Masking by harmonic complexes depends on the frequency content of the masker and its phase spectrum. Harmonic complexes created with negative Schroeder phases (component phases decreasing with increasing frequency) produce more masking than those with positive Schroeder phases (increasing phase) in humans, but not in birds. The masking differences in humans have been attributed to interactions between the masker phase spectrum and the phase characteristic of the basilar membrane. In birds, the similarity in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 27 publications
(17 reference statements)
5
16
2
Order By: Relevance
“…Thirdly, previous studies in normal-hearing birds have shown that maskers with C values of +1.0 and −1.0 produce similar amounts of masking (Leek et al 2000; Dooling et al 2001; Lauer et al 2006). Interestingly, BWC show a larger difference in the amount of masking by these maskers (4.94 dB) than non-BWC (1.07 dB) (Dooling et al 2001; Lauer et al 2006).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Thirdly, previous studies in normal-hearing birds have shown that maskers with C values of +1.0 and −1.0 produce similar amounts of masking (Leek et al 2000; Dooling et al 2001; Lauer et al 2006). Interestingly, BWC show a larger difference in the amount of masking by these maskers (4.94 dB) than non-BWC (1.07 dB) (Dooling et al 2001; Lauer et al 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Average thresholds for detecting 2800 Hz tones in harmonic complex maskers for BWC are shown in Figure 4 along with mean thresholds replotted from Lauer et al (2006) for three normal-hearing non-BWC tested using identical methods. Several of the non-BWC also participated in Experiments 1 and 2 of the present study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations